THYROID DYSFUNCTION AMONG TYPE 2 DIABETICS AND NON-DIABETICS: A CASE CONTROL STUDY - Suhail Marfani; Raisa Shaikh; Sama Ul Haque; Zafar, Adeel; Naila Ikram; Zainab Farooq (Pakistan Journal of Physiology, 2020)
Background: Type 2 diabetes mellitus (T2DM) and thyroid disorders are most commonly encountered endocrinal disorders. The objective of this study was to evaluate thyroid dysfunction among type 2 diabetics and non-diabetics. Methods: This case control study was conducted for 6 months from Jul to Dec 2023, and patients were included through non-probability convenient sampling technique. Patients were divided into two groups (150 type 2 diabetics and 150 non-diabetics). Diagnosed cases of type 2 diabetes confirmed by using ADA criteria for minimum 6 months were included. Patients with diabetic ketoacidosis, chronic renal failure or using drugs affecting thyroid functions were excluded. SPSS-23 was used for data analysis. Independent t-test was applied and p<0.05 was considered statistically significant. Results: Total 49.3% of patients were diabetic for 1–5 years. Mean serum T3 was 110.4±40.74 ng/dL in diabetic group and 154.7±11.35 ng/dL in non-diabetic group (p<0.001). Mean serum T4 level was 6.89±2.90 µg/dL in diabetic group and 8.76±0.94 µg/dL in non-diabetic group (p<0.01). Mean TSH level was 7.44±7.29 mIU/mL in diabetic group and 2.73±1.67 mIU/mL non-diabetic group (p<0.0001). Mean HbA1c was 7.49±0.84% in diabetic group and 5.78±0.51% in non-diabetic group (p<0.001). Conclusion: Diabetic patients were at a higher risk for thyroid dysfunction. Significantly lower level of T3, T4, and higher levels of TSH were reported among diabetics, compared to non-diabetics. Subclinical hypothyroidism was the most frequently reported thyroid disorder. Pak J Physiol 2024;20(4):24-7, DOI: https://doi.org/10.69656/pjp.v20i4.1745